Mobility Management Scheme For Hierarchical Mobile IPV6 Networks - Siddig Elhage, Elshima (2006)
Mobile IPv6 (MIPv6) was the best solution to fulfill the need of having Internet connection anywhere and anytime, but intrinsically it is not capable of solving all the problems and difficulties of handover and roaming authorization needed for future networks. The proposed F-HMIPv6 performs the handover process on the mobility anchor point level rather than the access routers level in the normal combination of the two approaches. It offers a pre-check for the handover availability through the new proposed and implemented entity, auxiliary node.